PEMBERDAYAAN KELOMPOK TANI DI DESA NIRAMESI KABUPATEN ENDE MELALUI PEMBUATAN PUPUK ORGANIK DARI KOTORAN TERNAK - Doa, Hamsa; Ngapa, Yulius Saprianus Dala; Tima, Maria Tensiana (Universitas katolik Musi Charitas, 2025)
Purpose: This community service activity aims to reduce the dependence of the Niramesi village community on chemical fertilizers, which has contributed to declining soil fertility and reduced agricultural sustainability. The program is designed to encourage a transition toward organic fertilizer utilization by strengthening community knowledge, skills, and awareness of environmentally friendly agricultural practices while optimizing local resources to support productivity and economic improvement. Design Methodology Approach: The program was implemented through a community empowerment approach involving structured training and continuous mentoring. Activities included education on the negative impacts of chemical fertilizer overuse, hands on training in organic fertilizer production using locally available livestock manure, and technical assistance during the application process. The approach emphasized participatory engagement to ensure knowledge transfer and practical adoption by community members. Findings: The results indicate increased community understanding of sustainable fertilization practices and improved technical skills in producing and applying organic fertilizer. Participants demonstrated reduced reliance on chemical fertilizers and greater confidence in utilizing organic alternatives derived from local resources. The program also fostered stronger collaboration between the university and the community. Practical Implications: The adoption of organic fertilizer practices contributes to improved soil quality, enhanced agricultural productivity, and reduced production costs. By utilizing livestock waste, the program supports environmentally responsible farming while strengthening local economic resilience and farmer independence. Originality Value: This program highlights a community based empowerment model that integrates local resource utilization with continuous university mentoring. The approach reinforces the role of universities as catalysts for sustainable agriculture and community welfare through long term, practice oriented partnerships.